Behavior of mungbean strains in field conditions at Itaguaí, Rio de Janeiro - Sayão, Flavio A.D.; Brioso, Paulo S.T.; Duque, Fernando F. (Pesquisa Agropecuaria Brasileira, 1991)
An experiment was conducted at the field station of the Centro Nacional de Pesquisa de Biologia do Solo (CNPBS)/EMBRAPA, Seropédica, Itaguaí, RJ, Brazil, to evaluate the agronomical behavior of 25 cultivars of mungbean (Vigna radiata (L.) Wilczek), in a Red-Yellow Podzolic soil, Itaguaí series, in the rainy season of 1988/89. The best total grain yield was 1520 kg/ha for VC-3012B cultivar, and 1484 kg/ha for VC-3301A. The average yield of the 25 cultivars was 1239 kg/ha. The pod numbers/plant, grain numbers/pod, empty loculi/pod and nodule number/plant had significant differences. The dry nodule weight/plant and dry matter weight and total N of aerial plant part had no significant differences. Four grain harvest were done, giving, the first and the third, together, 91,1% of the total yield, indicating the possibility of having only two harvests, even in the rainy season.